A Cooperative OSDA Blueprint for Highly Siliceous Faujasite Zeolite Catalysts with Enhanced Acidity Accessibility. Issue 45 (7th October 2021) - Ke, Quanli; Khalil, Ibrahim; Smeyers, Brent; Li, Zheng; de Oliveira‐Silva, Rodrigo; Sels, Bert; Sakellariou, Dimitrios; Dusselier, Michiel
Abstract: A cooperative OSDA strategy is demonstrated, leading to novel high‐silica FAU zeolites with a large potential for disruptive acid catalysis. In bottom‐up synthesis, the symbiosis of choline ion (Ch + ) and 15‐crown‐5 (CE) was evidenced, in a form of full occupation of the sodalite (sod) cages with the trans Ch + conformer, induced by the CE presence. CE itself occupied the supercages along with additional gauche Ch +, but in synthesis without CE, no trans was found. The cooperation, and thus the fraction of trans Ch +, was closely related to the Si/Al ratio, a key measure for FAU stability and acidity. As such, a bottom‐up handle for lowering the Al‐content of FAU and tuning its acid site distribution is shown. A mechanistic study demonstrated that forming sod cages with trans Ch + is key to the nucleation of high‐silica FAU zeolites. The materials showed superior performances to commercial FAU zeolites and those synthesized without cooperation, in the catalytic degradation of polyethylene. Abstract : A cooperative OSDA blueprint for high‐silica FAU zeolites (Si/Al >6) is presented. Only via true cooperation with a crown ether, could trans choline occupy the sod cages of the growing zeolite. Raman‐tracking of the crystallization points to nucleation by the formation of sod‐ rather than D6R‐ or super‐cages. Reliably low Al‐contents and a unique acidity is thus obtained for a relevant catalytic topology, as validated by plastic waste cracking.